PENGARUH NILAI VARIANS DAN STEP SIZE TERHADAP MEAN SQUARE DEVIATION PADA LEAST MEAN SQUARE FILTER ADAPTIF - Pagiling, Luther (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Variant value and step size effect of an adaptive filter are required to know how system to work, how fast the reachable system stability and how big adaptive filter can be able to eliminate the noise. At LMS adaptive, all of variants value stability systems reached and assess variant of input influence mean square deviation (MSD) con-vergence.Stability of system reached at value of step size, correlation matrix ( R ), and to the number of certain element weight vector. Normalization data convergence by MSD is compared to bigger of linear error convergence from MSD, that way the things of compared to bigger MSD simulation convergence of MSD Theory. MSD Convergence compare diametrical with input variant value and assess step size.